Musical Traditions of Samarkand in the Early 20th Century (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
In this article, the services rendered by the famous Samarkand vocalists, master–disciple Shashmaqom performers Hoji Abdulaziz Abdurasulov and Qori Siroj Yusupov, in Uzbek musical art, as well as their creative research carried out in the field of art, are discussed. All information in the article is written on the basis of historical facts. Musical terminology is also used.